(untitled) (European Journal of Health Research, 2021)
Inflammatory bowel disease is a disease that is still somewhat unknown where we find important nutritional and metabolic implications. Nutritional due to the degree of malnutrition that it entails in the same way because the hypothesis that good nutrition could be the primary treatment of the disease. Methodology: Nutrition should be considered an integral component in the management of patients with IBD: A search was carried out in the most frequented databases such as Dialmet and Pubmed. Also, searches have been made in the Virtual Health Library (VHL), finding no results in it. Results: we have obtained from three studies different characteristics of IBD, where we have been able to obtain results from each one of them separately to be able to finalize the conclusions. Discussion / Conclusions: Nutrition should be considered an essential component in the management of IBD. This statement is contrasted with the studies reviewed in this work. Nutritional assessment is the first link in the chain in nutrition management. Other evidence found in our review is that there is no specific food that is harmful for IBD. It cannot be demonstrated that there is a component of the diet that is associated with the risk, triggering or worsening of inflammatory activity. However, outbreak patients should only avoid foods that their body consistently does not tolerate adequately and may increase or worsen outbreak symptoms.